OPPRESSION IN THE CHARACTERS CELIE AND NETTIE IN â€œTHE COLOR PURPLEâ€ BY ALICE WALKER - Hernani, Lena (JURNAL LITERARY CRITICISM, 2016)
This thesis discusses about the oppression in the characters of Celie and Nettie in The Color Purple novel written by Alice Walker. The purposeof this thesis are to analyze the forms of oppression experienced by a female character who was 14 years old mistreatment of his father, Alphonso and to find the correlation between the oppression happened in the novel and theory postcolonialism by Frantz Fanon. The researcher used a qualiative data. The techniques are by reading the novel, underlining the keywords from the novel that can show the oppression forms, understanding the theory to find the correlation between the novel and the theory. Various forms of oppression character Celie as physical violence, verbal and emotional. The theory used to analyze this thesis is the theory postcolonialism explained by Franz Fanon. In the theory, the oppression of human beings is destructive of the human mental. Based on the analysis of the authors that many forms of oppression experienced by the characters in the novel especially Celie and Nettie. It is concluded, oppression is a very destructive action of a character souls undergo such treatment. Keywords : oppression, characters, mental destruction